PKM Teknologi Fermentasi Tape Jusinta di Pondok Pesantren Puteri Yatama Mandiri Kabupaten Gowa - Nurhayani H. Muhiddin; Ratnawaty Mamin; Hasanuddin Hasanuddin (Universitas Negeri Makassar, 2020)
The target partners in the Public Partnership Program (PKM) of Jusinta Tape Fermentation technology are students at the XII grade SMA Yatama Mandiri Islamic Boarding School, Gowa Regency. The location of the Islamic boarding school is in the area of Pallangga Subdistrict, Gowa Regency, which has the first highest cassava production and second highest sweet potatoes production land in South Sulawesi.. The implementation of activities is supported by the field of expertise of the implementing team related to the results of research in the form of a tape product called